The correlation between polymorphism of interleukin 3 receptor alpha Rs6603272 G/T gene with negative symptoms in Bataknese schizophrenia patients - Dika Asrika Asrul; Elmeida Effendy; Mustafa Mahmud Amin; Vita Camellia; Zulham Yamamoto (Medicinski glasnik, 2026)
Aim: There are many studies about the correlation between Bataknese and schizophrenia patients, one of the most common ethnic in Indonesia. Cytokine and its’ receptor disorder is one of the scope of immunology research in schizophrenia. Interleukin 3 (IL-3) is an important cytokine with various biologic roles in immune response. We would like to determine the association between the polymorphism of IL3RA gene with negative symptoms in Bataknese schizophrenia patients. Methods: This study used comparative case control approach. The negative symptoms were assessed using Positive and Negative Syndrome Scale (PANSS). Blood sampling and deoxyribonucleic acid (DNA) isolation used salting out method followed by IL3RA RS6603272 G/T genotype identification using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. The data were analysed using χ2 and Kruskal Wallis test. A p<0.05 was considered statistically significant. Results: Two hundred participants were divided into schizophrenia and healthy control groups evenly. G alleles (49.5% and 50.5%) and GT genotypes (49% and 53%) were the most common alleles and phenotypes in both groups with no significant difference in both groups (p>0.05). The analysis also did not reveal significant correlation between the polymorphism of IL3RA RS6603272 G/T with the negative symptoms of schizophrenia (p > 0.05). Conclusion: There was neither significant difference of the presence of G and T alleles, also GG, GT, and TT genotypes between two groups nor the correlation between polymorphism of IL3RA RS6603272 G/T with schizophrenia negative symptoms.
Keywords: Bataknese; IL3RA RS6603272 G/T gene; polymorphism; Schizophrenia negative symptoms.